1911-1918 Yılları Arasında Türk Yurdu Dergisine Konu Olan Bazı Tartışma ve Polemikler / Some Polemics and Discussions which were Subjected In Turk Yurdu Magazine Between 1911-1918 - Erkan, Ümmet (Journal of History Culture and Art Research, 2016)
Some Polemics and Discussions which were Subjected In Turk Yurdu Magazine Between 1911-1918 Abstract Started to press in 1911, The Turk Yurdu Magazine which is the longest press in Turkish Nationalism, leaded by the Turks in Russia whose aims were the Turkish Nation’s going up in all areas. This article examines some polemics, letters and replies for these letters took place in the issues between the years 1911/1918. In this polemics, the topics of what should be understood from the simplification of Turkish and its boundaries, the lack of idealism in education, education with Turkish language, the damages of minority schools on the social life of Ottoman people, the success of the programs of Tanzimat, the effects of national ID on religious ID and the like were discussed. These polemics which the authors of Turk Yurdu and the other intellectuals who took place in the discussion from different newspapers and magazines got a very rich content. This article focuses on the topics which the debates revolves around and and the intellectual discussions about them. 1911-1918 Yılları Arasında Türk Yurdu Dergisine Konu Olan Bazı Tartışma ve Polemikler Öz Türk Yurdu Dergisi 1911 yılında yayın hayatına başlamış, Türk milliyetçiliinin en uzun soluklu yayın organıdır. Rusya Türklerinin öncülük ettiği dergide Türklüğün her alanda yükselmesi amaçlanmıştır. Bu makalede Türk Yurdu dergisinin 1911-1918 yılları arasındaki sayılarından yola çıkılarak dergideki bazı kalem tartışmaları, mektuplar ve onlara verilen cevaplar incelenecektir. Bu kalem tartışmalarında Türkçenin sadeleştirilmesinden ne anlaşılması gerektiği ve sınırları, eğitimde ideal eksikliği, eğitim dilinin Türkçe olması ve azınlık okullarının Osmanlı sosyal bünyesine verdiği zararlar, Tanzimatçı reform programının başarılı olup olmadığı ve nedenleri, milli kimliğin dini aidiyete zarar verip vermeyeceği konuları ele alınacaktır. Türk Yurdu dergisi yazarları ile dönemin diğer önemli entelektüellerinin çeşitli gazete ve dergilerde dâhil olduğu bu kalem tartışmaları zengin bir muhteva kazanmıştır. Bu tartışmalar dönemin entelektüel fikir hareketleri ve siyasi akımlar hakkında önemli bilgiler içermektedir. Bu araştırma, yapılan tartışma ve polemiklerin hangi konular etrafında yoğunlaştığını ve Türk Yurdu dergisinin bu tartışma ve polemiklerde ne tür bir yöntem izlediğini ortaya koymaktadır.